National Health Insurance Participants Satisfaction in General Polyclinic Services at First Level Healthcare Facilities - Thinni Nurul Rochmah1 , Djazuly Chalidyanto1 , Ernawaty1 , Rachmad Suhanda2,3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The need of health services, especially at first level healthcare facilities (FKTP) for the community to accessbasic health services has increased in Indonesia. This condition related to the regulation for the entire citizenin Indonesia to become a National Health Insurance (JKN) participant. Some problems related to the servicesstill occur, such as queues length and non-optimal examination process. This research aimed to analyzepatients’ satisfaction in general polyclinic services differences in FKTP. This was an observational researchwith a cross-sectional study using primary data from both types of FKTP (Puskesmas and Non-Puskesmas)as the healthcare provider in two cities of East Java. The number of research respondents was 219 in 20FKTP. The sampling method used was proportional random sampling technique. Patients’ satisfactionscores obtained from the two types of FKTP were analyzed using independent sample T Test. The resultsobtained was the satisfaction score in Puskesmas and Non-Puskesmas exceeded 95%. Patients’ satisfaction inPuskesmas was significantly higher than Non-Puskesmas (p = 0.01). Out of the six dimensions, dimensionsof service ability and aesthetics in exception, the other four dimensions had significant differences. Theresults provide recommendation that FKTP should improve their services from various dimensions.